How English as a Foreign Language (EFL) University Students Understand the Pronunciation of Adjectives Ending in -ed - Charpentier Jiménez, William (2019)
This article looks at how EFL university students understand the pronunciation of adjectives that end in -ed. The goal is to determine the extent to which students are able to follow pronunciation rules and exceptions of -ed inflections when used as adjectives. The quantitative study presents data gathered from a 20-item multiple choice test that was taken by 61 students.  Overall results reveal that students obtained low scores (M = 7.33, SD = 1.51, n = 61) and even lower scores (M = 2.00, SD = 2.33, n = 61 for non-governed-rule -ed endings) with regards to following rule-governed pronunciation patterns. On average, students were able to identify -ed endings pronounced /ɪd/ 8.2% of the times, followed by /d/ (7.31%) and /t/ (6.49%). Students scored lowest for non-standard pronunciation of participial adjectives (2.72%). The results reveal that students have not yet mastered the rules for the pronunciation of participial adjectives ending in -ed. The author proposes that changes be made to the curriculum and the design of the materials and that current classroom practices be assessed in order to help improve student pronunciation. Lastly, the author highlights the need to conduct further research focusing on pronunciation and auditory perception to attain this goal.